2019
DOI: 10.1038/s41598-019-52085-w
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine modulates inflammatory autoimmune responses through Nurr1 in autoimmune diseases

Abstract: For over a half-century the anti-malarial drug chloroquine (CQ) has been used as a therapeutic agent, alone or in combination, to treat autoimmune diseases. However, neither the underlying mechanism(s) of action nor their molecular target(s) are well defined. The orphan nuclear receptor Nurr1 (also known as NR4A2) is an essential transcription factor affecting the development and maintenance of midbrain dopaminergic neurons. In this study, using in vitro T cell differentiation models, we demonstrate that CQ ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 49 publications
3
42
0
Order By: Relevance
“…Additionally, CQ directly modulates DCs by inducing iNOS and pSTAT1 expression, and the lack of these molecules abrogated the tolerogenic phenotype of CQ-treated DCs [ 30 , 32 ]. A similar increase in Foxp3 + Treg cells in models of inflammatory bowel disease and lupus was observed [ 53 , 54 ]. CQ directly induced Foxp3 expression in T cells in a Nurr1-dependent manner [ 53 ].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Additionally, CQ directly modulates DCs by inducing iNOS and pSTAT1 expression, and the lack of these molecules abrogated the tolerogenic phenotype of CQ-treated DCs [ 30 , 32 ]. A similar increase in Foxp3 + Treg cells in models of inflammatory bowel disease and lupus was observed [ 53 , 54 ]. CQ directly induced Foxp3 expression in T cells in a Nurr1-dependent manner [ 53 ].…”
Section: Discussionsupporting
confidence: 62%
“…A similar increase in Foxp3 + Treg cells in models of inflammatory bowel disease and lupus was observed [ 53 , 54 ]. CQ directly induced Foxp3 expression in T cells in a Nurr1-dependent manner [ 53 ]. Thus, the literature data show that CQ induces STAT1 in DCs, T-bet in Th17 cells and Nurr1 in naïve T cells [ 32 , 53 , 54 ].…”
Section: Discussionsupporting
confidence: 62%
“…9 Ischemia, CQ absence of caspase-1/11signaling alter oxidative metabolism in muscle stellate cells (MuSC). Seahorse™ analysis of maximal respiration, spare respiratory capacity (including %), non-mitochondrial oxygen consumption, ATP production, and coupling efficiency in MuSC harvested from tibialis anterior (TA) of nonischemic and ischemic limbs of C57Bl6/J (WT) and caspase1/11KO mice at 21 days after femoral artery ligation (FAL) treated with either PBS or CQ (50 mg/kg); * p < 0.05, **p < 0.01, ***p < 0.001 replacement and fibrosis may result from inflammation, and since CQ is known to be anti-inflammatory (Park et al 2019) we hypothesized that CQ would reduce inflammatory markers, including those associated with inflammasome signaling, such as caspase-1. Instead, we found that CQ increased caspase-1 expression, cleavage and activity in C2C12 mouse myoblasts without increasing cell death (Xu et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Fat replacement and brosis may result from in ammation, and since CQ is known to be antiin ammatory (46) we hypothesized that CQ would reduce in ammatory markers, including those associated with in ammasome signaling, such as caspase-1. Instead, we found that CQ increased caspase-1 expression, cleavage and activity in C2C12 mouse myoblasts without increasing cell death (2).…”
Section: Discussionmentioning
confidence: 99%